KUALITAS PELAYANAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KETENAGAKERJAAN (Studi tentang pemberian pelayanan BPJS Ketenagakerjaan bagi tenaga kerja di Kantor BPJS Cabang Rungkut Surabaya) - Hidayah, Lina Nur; Santoso, Teguh (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
In the public service there are many complaints that occur during the service process, the goal of increasing the quality of service is an important part in serving the community effort to improve the quality standard of service that covers all aspects of service. So that the problem in the quality of service Social Security Employment Agency in providing services for labor. Based on the theory Kotler, about the quality of service. Researchers use assessment indicators Tangible, Reliability, Responsiveness, Confidence and, Empaty. As for supporting this study, researchers used a qualitative method by interviewing, questionnaires, observation and documentation. Data analysis techniques by means of editing, classification of data (data Internal and external) and data analysis. The target is the author of community service performed properly. The results showed that the quality of services performed by the Social Security Agency Employment Branch Rungkut already good. Facilities and infrastructure, responsiveness, reliability, assurance and empathy assessed majority of people are already well as for suggestions for BPJS Employment Branch Rungkut that regard waiting room capacity for less spacious waiting room service, especially the seating in waiting queues are less numerous and officers checking the initial data and the grantor there should be information itself is not merged into one Keywords: Tangible, Reliability, Responsiveness, Confidence and, Empaty.